2020
DOI: 10.12963/csd.19682
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Related to Self-perceived Hearing Handicap in the Elderly with Moderate to Moderately-severe Hearing Loss

Abstract: Objectives:The aims of this study were to compare the performance related to audiometric, cognitive function, and depression variables between the elderly with mild-to-moderate hearing handicap and the elderly with severe hearing handicap, to identify which factors are correlated with their self-perceived hearing handicap, and to determine which factors can distinguish the elderly with mild-to-moderate hearing handicap from the elderly with severe hearing handicap. Methods: A total of 22 elderly patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…Patients with noise-induced hearing loss in the study reported more severe hearing loss and more severe subjective tinnitus than patients with presbycusis. It showed the same results as previous studies [10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients with noise-induced hearing loss in the study reported more severe hearing loss and more severe subjective tinnitus than patients with presbycusis. It showed the same results as previous studies [10].…”
Section: Discussionsupporting
confidence: 89%
“…Patients with noise-induced hearing loss were defined as those with a history of exposure to noise, such as workers in the mining and machinery industries. The hearing threshold was ≥25 dB, as calculated using the six-division method ((500 Hz + 2 × 1 kHz + 2 × 2 kHz + 4 kHz)/6) on PTA [9,10]. Patients with presbycusis were defined as those aged ≥65 years without a history of noise exposure, with a hearing threshold of ≥25 dB as calculated using the six-division method on PTA.…”
Section: Subjectsmentioning
confidence: 99%
“…Hearing threshold tests were performed at frequencies of 500, 1000, 2000, 3000, 4000, and 6000 Hz, measured in that order, followed by a retest at 1000 Hz, with air conduction measured at a frequency of 500 Hz. Pure tone audiometry was performed using the standard hexadecimal method, by measuring the air conduction values of each ear at four frequencies (500, 1000, 2000, and 4000 Hz) and calculating their sum using the equation: (500 Hz + 2 × 1000 Hz + 2 × 2000 Hz + 4000 Hz)/6 [ 14 , 15 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…국내 청각장애인 수는 꾸준히 증가하는 추세로, 최근 급격한 청각장애인 증가 원인 중 하나는 인구 고령화이다 (Lim & Chae, 2011;Shin, 2013). 2025년 국내 초고령사회의 진입 (Kim & Han, 2017;Lee, 2017)과 함께 노화성 난청으로 인한 난청 인 구의 증가 (Kim & Yeo, 2015;Williger & Lang, 2014) (Kang, 2022;Lee et al, 2020;Son & Heo, 2018;Thak et al, 2022)…”
unclassified